Community Engagement in Liberia: Routine Immunization Post-Ebola. (1st March 2017) - Bedford, Juliet; Chitnis, Ketan; Webber, Nance; Dixon, Phil; Limwame, Ken; Elessawi, Rania; Obregon, Rafael
Abstract : A national integrated polio, measles, and deworming campaign was implemented across Liberia May 8–14, 2015. The community engagement and social mobilization component of the campaign was based on structures that had been invested in during the Ebola response. This article provides an overview of the community engagement and social mobilization activities that were conducted and reports the key findings of a rapid qualitative assessment conducted immediately after the campaign that focused on community perceptions of routine immunization in the post-Ebola context. Focus group discussions and interviews were conducted across four counties in Liberia (Montserrado, Nimba, Bong, and Margibi). Thematic analysis identified the barriers preventing and drivers leading to the utilization of routine immunization. Community members also made recommendations and forwarded community-based solutions to encourage engagement with future health interventions, including uptake in vaccination campaigns. These should be incorporated in the development and implementation of future interventions and programs.